Gene expression profile in experimental frozen-thawed ovarian grafts treated with scaffold-base delivery of adipose tissue-derived stem cells (Clinics, 2022)
Purpose: Gelfoam scaffold is a feasible and safe non-invasive technique for Adipose tissue-derived Stem Cell (ASC)-delivery in the treatment of frozen-thawed ovarian autografts. This study seeks to analyze the genes expression profile of rat frozen-thawed ovarian autografts treated with scaffold-based delivery of adipose tissue-derived stem cells.Methods: Eighteen adult Wistar rats were distributed into three groups: Control (frozen-thawed only); Group 1 (G1) and Group 2 (G2) (frozen-thawed ovaries treated with culture medium or ASC, respectively). Both treatments were performed immediately after autologous retroperitoneal transplant with scaffold-based delivery. The ovarian grafts were retrieved 30 days after transplantation. Quantitative gene expression (qPCR) for apoptosis, angiogenesis, and inflammatory cytokines (84 genes in each pathway) were evaluated by RT-PCR. Graft morphology (HE), apoptosis (cleaved-caspase-3), neoangiogenesis (VEGF), and cellular proliferation (Ki-67) were assessed.Results: In grafts treated with ASC, the apoptosis pathway showed the highest number of genes over-regulated – 49 genes – compared to inflammation cytokines and angiogenesis pathway – 36 and 23 genes respectively, compared to grafts treated with culture medium. Serpinb5 family was highlighted in the angiogenesis pathway and Cxcl6 in the inflammation cytokines pathway. In the apoptosis pathway, the most over-regulated gene was Capsase14. ASC treatment promoted the reduction of cleaved caspase-3 in the theca internal layer and increased cell proliferation by Ki-67 in the granulosa layer without altering VEGF. A mild inflammatory infiltrate was observed in both groups.Conclusion: ASC therapy in rat frozen-thawed ovarian autografts promoted an abundance of genes involved with apoptosis and inflammatory cytokines without compromising the ovary graft morphology and viability for short time. Further studies are necessary to evaluate the repercussion of apoptosis and inflammation on the graft in the long term.